Anomalous Diffusion in Random-Walks With Memory-Induced Relocations - Masó-Puigdellosas, Axel; Campos, Daniel; Méndez, Vicenç (Frontiers in Physics, 2019)
In this minireview we present the main results regarding the transport properties of stochastic movement with relocations to known positions. To do so, we formulate the problem in a general manner to see several cases extensively studied during the last years as particular situations within a framework of random walks with memory. We focus on (i) stochastic motion with resets to its initial position followed by a waiting period, and (ii) diffusive motion with memory-driven relocations to previously visited positions. For both of them we show how the overall transport regime may be actively modified by the details of the relocation mechanism.